2018
DOI: 10.1515/hukin-2017-0131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Post-Activation Potentiation Warm-Ups on Repeated Sprint Ability in Soccer Players from Different Competitive Levels

Abstract: This study aimed to compare the effects of a traditional warm-up with two post-activation potentiation (PAP) warm-up strategies on the repeated sprint ability (RSA) of soccer players from national (NL) and regional (RL) competitive levels. Sixteen young players (NL, n = 8, age = 20.7 ± 1.4 y, body mass = 68.5 ± 7.0 kg, body height = 177.4 ± 5.2 cm; RL, n = 8, age = 20.8 ± 1.0 y, body mass = 68.7 ± 4.0 kg, body height = 176.6 ± 5.6 cm) were recruited to complete a traditional warm-up (CONTROL), a PAP warm-up in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 45 publications
0
32
1
7
Order By: Relevance
“…Traditionally, swimmers warm-up is composed of moderateintensity stimuli and short stimuli at high intensity, not exceeding 1,500-m and usually the competition styles are used (Kilduff et al, 2011). Nonetheless, conditioning activity (CA) of highintensity and short-duration has been the focus of attention in swimming, especially in sprint events (Hancock et al, 2015;Sarramian et al, 2015;Barbosa et al, 2016;Cuenca-Fernández et al, 2017;Sanchez-Sanchez et al, 2018). CA is characterized by previous voluntary contractions of the requested musculature in the task of interest from complex exercises with maximum or close to maximum loads (Hodgson et al, 2005;Batista et al, 2007;Cuenca-Fernández et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, swimmers warm-up is composed of moderateintensity stimuli and short stimuli at high intensity, not exceeding 1,500-m and usually the competition styles are used (Kilduff et al, 2011). Nonetheless, conditioning activity (CA) of highintensity and short-duration has been the focus of attention in swimming, especially in sprint events (Hancock et al, 2015;Sarramian et al, 2015;Barbosa et al, 2016;Cuenca-Fernández et al, 2017;Sanchez-Sanchez et al, 2018). CA is characterized by previous voluntary contractions of the requested musculature in the task of interest from complex exercises with maximum or close to maximum loads (Hodgson et al, 2005;Batista et al, 2007;Cuenca-Fernández et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is little research regarding the effects of heavy resistance exercise on subsequent performance in soccer (Hammami et al, 2018). Some authors indicated that heavy resistance exercise may improve subsequent jump and COD (Zois et al, 2011), repeated sprints (Low et al, 2015; Sanchez-Sanchez et al, 2018) and single linear sprint (McBride et al, 2005; Tillin and Cooke, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was also reported that pre-loading may increase muscle stiffness (Moir et al, 2009). Previous studies have suggested that PAP responses might be dependent on individual characteristics (Sanchez-Sanchez et al, 2018). For instance, stronger subjects exhibited a greater PAP response when compared with weaker counterparts (Seitz and Haff, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies examining the PAP phenomenon have employed heavy (75–95% with one repeat maximum) isotonic resistance exercises as the preload stimulus, with some authors also supporting the use of maximal isometric conditioning contractions [11]. The PAP effect depends on the balance between fatigue and neuromuscular potentiation [12], which in turn depends on the type of exercise, volume, intensity, and recovery time [13].…”
Section: Introductionmentioning
confidence: 99%